2022
DOI: 10.3390/sym14071451
|View full text |Cite
|
Sign up to set email alerts
|

Regularity and Travelling Wave Profiles for a Porous Eyring–Powell Fluid with Darcy–Forchheimer Law

Abstract: The goal of this study is to provide analytical and numerical assessments to a fluid flow based on an Eyring–Powell viscosity term and a Darcy–Forchheimer law in a porous media. The analysis provides results about regularity, existence and uniqueness of solutions. Travelling wave solutions are explored, supported by the Geometric Perturbation Theory to build profiles in the proximity of the equation critical points. Finally, a numerical routine is provided as a baseline for the validity of the analytical appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Recently with a degenerate difusivity, Eyring-Powell viscosity term, and a Darcy-Forchheimer law in the porous medium, the authors in [20] obtained the traveling wave profle and showed the existence of the asymptotic solution using the geometric perturbation theory. Tey also showed the existence of an exponential profle of the solution under an asymptotic approximation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently with a degenerate difusivity, Eyring-Powell viscosity term, and a Darcy-Forchheimer law in the porous medium, the authors in [20] obtained the traveling wave profle and showed the existence of the asymptotic solution using the geometric perturbation theory. Tey also showed the existence of an exponential profle of the solution under an asymptotic approximation.…”
Section: Introductionmentioning
confidence: 99%
“…When the literature is reviewed carefully, the analytical solutions of these type models are missing, most studies consider numerical solutions (Ali et al ., 2018; Oke, 2021; Bilal and Ashbar, 2020; Diaz et al. , 2022a, b, c, d). First, using appropriate similarity transformation, the equations are reduced to dimensionless form (NODE).…”
Section: Introductionmentioning
confidence: 99%